PREVALENCE, IDENTIFICATION, AND ANTIMICROBIAL SUSCEPTIBILITY TESTING OF Acinetobacter baumannii COMPLEX & PSEUDOMONAS SPECIES IN A TERTIARY CARE CENTRE IN THE EASTERN PART OF BIHAR. - Anwar, Md Sahil; Biswas, Priyanka Paul; Nandy, Shyamasree; Akhter, Kahkashan; Wari, Md. Nahidul; Sen, Aninda (Student’s Journal of Health Research Africa, 2025)
Background Acinetobacter baumannii and Pseudomonas species have emerged as significant pathogens in healthcare-associated infections, showing resistance to multiple antibiotics, which complicates treatment options. Both organisms exhibit inherent and acquired resistance, making infections difficult to manage. Aim The study aimed to isolate, identify, and determine the antimicrobial susceptibility patterns of Acinetobacter baumannii and Pseudomonas species from clinical samples in a tertiary care center. Materials & Methods This hospital-based cross-sectional study was conducted between November 2023 and September 2024 at a tertiary care center in Northern Bihar. A total of 60 isolates of Acinetobacter baumannii and Pseudomonas species were identified using VITEK 2. Antibiotic susceptibility testing was performed using the MIC microbroth dilution technique. Results Out of 1058 clinical samples, 186 were positive for bacterial growth. Acinetobacter baumannii complex was isolated from 36 samples, and Pseudomonas species from 23. The sociodemographic results revealed that the majority of patients were in the 21-30 age group, with a higher prevalence of males (59.3%) compared to females (40.6%). The majority of Acinetobacter baumannii isolates (44.4%) were from sputum, followed by blood (30.5%). Resistance to multiple antibiotics, including piperacillin/tazobactam and meropenem, was observed in Acinetobacter baumannii, with strains isolated from urine showing 100% resistance to several antibiotics. Pseudomonas aeruginosa from sputum samples showed sensitivity to piperacillin/tazobactam and meropenem, while those from pus samples exhibited resistance to ceftazidime and imipenem. Conclusion Nitrofurantoin is an effective option for urinary tract infections caused by Acinetobacter baumannii, while piperacillin/tazobactam and meropenem are recommended for empirical treatment of Pseudomonas aeruginosa. Resistance patterns highlight the need for stringent infection control measures to prevent the spread of multidrug-resistant organisms. Recommendation Enhanced infection control and cautious use of antibiotics are essential to combat multidrug-resistant infections in healthcare settings.